Optimization of the Technology Sector Stock Portfolio during the Covid-19 Pandemic Using the Markowitz Model - Grace Meisel; Marlina Setia Sinaga (Asian Journal of Community Services, 2022)
Stock investment in Indonesia has grown quite rapidly in recent years and has attracted the attention of many people . When investing, analysis is needed to get future profits by minimizing stock risk. One of the ways that can be used to minimize risk is to form an optimal portfolio using the Markowitz model. The technology sector is one of the stock sectors that has progressed because of the high public interest in technology-related matters during the Covid-19 pandemic. In this study , the optimal portfolio is a portfolio containing EMTK with a weight of 63% and TFAS with a weight of 37% which produces an expected return value of 0.007488 ( 0.7488%) and a risk value of 0.035000 (3.5%).